2009
DOI: 10.1149/1.3031596
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Temperature-Dependent Characteristics of Passivated In[sub 0.2]Ga[sub 0.8]AsSb∕GaAs High-Electron-Mobility Transistors

Abstract: This work investigates improved performance of dilute-antimony-channel normalIn0.2normalGa0.8AsSb∕GaAs high-electron mobility transistors (HEMTs), grown by a molecular beam epitaxy system, with (NnormalH4)2normalSx or silicon nitride (SinormalNx) passivations. With the advantageous dilute-antimony-channel design to effectively improve the carrier transport property and carrier confinement capability and the sulfur passivation technique to annihilate the surface states, the proposed (NnormalH4)2normalSx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was reported that sulfur treatment is very effective in reducing the surface states and surface recombination velocity in III-V compound semiconductors. [7][8][9][10][11][12] Of the various sulfur treatments, only the ͑NH 4 ͒ 2 S x treatment achieved promising results due to its capacity to etch the native oxide and the GaAs surface and to tie up the dangling bonds with sulfur on a freshly exposed prismatic GaAs surface. Although increasing immersion time promotes the performance, longer immersion time causes a higher surface roughness and a decline in the mobility of electrons by high sulfide contamination and chemical reaction.…”
mentioning
confidence: 99%
“…It was reported that sulfur treatment is very effective in reducing the surface states and surface recombination velocity in III-V compound semiconductors. [7][8][9][10][11][12] Of the various sulfur treatments, only the ͑NH 4 ͒ 2 S x treatment achieved promising results due to its capacity to etch the native oxide and the GaAs surface and to tie up the dangling bonds with sulfur on a freshly exposed prismatic GaAs surface. Although increasing immersion time promotes the performance, longer immersion time causes a higher surface roughness and a decline in the mobility of electrons by high sulfide contamination and chemical reaction.…”
mentioning
confidence: 99%
“…Clearly, V on and I G decrease and increase, respectively, as the temperature is increased due to the reduction of energy gap and enhanced tunneling mechanism with thermionic emission. 19 The increase of I G also degrades V on characteristic at high temperature. However, as compared with TE-gate device and other previous works of AlGaN/GaN HEMTs, 4 the studied EP-gate device shows higher turn-on voltage, lower gate leakage, and lower temperature variation rates at higher temperature ambiances.…”
Section: Resultsmentioning
confidence: 99%
“…In order to enhance the Schottky barrier height, depositing gate metals of high work function on wide-gap barrier layer has been attempted [10]. Other approaches using SiN [11][12] or sulfide [13][14] surface passivation techniques have also been studied. Besides, gate engineering technologies based on metal-insulator-semiconductor (MIS) or MOS structures have been studied by using atomic-layer-deposited (ALD) gate dielectrics [15], molecular beam epitaxy (MBE) deposited dielectrics [16], or InAlP oxides [17] to reduce the gate leakages.…”
Section: Introductionmentioning
confidence: 99%